Mainstreaming experience capitalization in Zimbabwe's department of research and specialist services - Gutsa, Freeman (Technical Centre for Agricultural and Rural Cooperation, 2019)
Following the different steps of an experience capitalization process to produce various knowledge products, DR&SS has been able to raise the visibility of its agricultural development projects and innovations. As a result, improved bean varieties have been taken up by local smallholders and the Ministry of Agriculture has adopted a policy recommendation submitted by the Department.